2014
DOI: 10.11648/j.ajns.20140301.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge among Saudi Diabetic Children/ Adolescent at Riyadh City

Abstract: Background Puberty is a period of rapid growth and hormonal changes and is often characterized by deterioration in glycemic control, and all of these factors may promote the development of diabetes complications . Diabetes Mellitus (DM) is a serious disease and it causes a number of chronic diseases such as Ketoacidosis, cardiovascular disease, renal failure, and neuropathy. The purpose of the study was to determine the knowledge level of student regarding diabetic management and its effect on their health. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(8 reference statements)
4
3
1
Order By: Relevance
“…Regarding to the adolescences residence, the finding of the study revealed that more than two third of them were rural. This finding is in the same line with (Moawad et al, 2014) who reported that, a great majority of diabetic children were live in rural areas, who study The Incidence and Prevalence of Type. I Diabetes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding to the adolescences residence, the finding of the study revealed that more than two third of them were rural. This finding is in the same line with (Moawad et al, 2014) who reported that, a great majority of diabetic children were live in rural areas, who study The Incidence and Prevalence of Type. I Diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…In this, study adolescences child didn't t know the complications of DM, but 18% of adolescences children know the most common complications of DM as low and high blood sugar, retinopathy, neuropathy. However, in immediate post-test, it is noticed that 64 % of adolescences children know the most common complications of DM This finding is in an accordance with (Moawad et al, 2014) who illustrated that diabetic children know these manifestations of diabetes mellitus hypo and Hyperglycemia after educational program. Moreover, this finding (Wong et al, 2003) state that children (DM) is a serious disease, and it causes a number of chronic diseases the same as Ketoacidosis, cardiovascular disease, renal failure, and neuropathy.…”
Section: Discussionsupporting
confidence: 80%
“…This level of knowledge is also found insu cient in another sub-Saharan African country like Malawi [9] but with not the same questionnaire as ours. Our rate is near to the same of 48.2% found in Saoudi Arabi [14] but less than those found in others settings such as 67.5% in Kuwait [15] and 86% in the USA [16], all with also a different questionnaire than ours. We used the same questionnaire as in France where the level of knowledge is 75% [17].…”
Section: Discussioncontrasting
confidence: 69%
“…20 According to Moawad et al, the majority of juvenile DM patients were also female. 21 Majority of the respondents were aged between 51 -60 years old, the mean age was 38.4 years ( Table 1). This is in accordance with the research of Alghamdi et al in 2017 which showed that the majority of DM patients are in the age range of 51 -60 years old because at that age they are usually very diligent in keeping their appointments with the health service facilities for examinations and treatment.…”
Section: Resultsmentioning
confidence: 99%